Critical Thinking Disposition and Dyadic Adjustment: The Moderator Role of Employment Status of Women - Ermiş, Ece Naz; YILDIRIM, MELİS SERAY ÖZDEN (My University, 2017)
Dyadic adjustment can be handled as a state in which there is an overall feeling of happiness and satisfaction with marriage. Women have become so much more active in work life over the past years that the changes in the roles of women also affect the communication with their husbands and as a result their dyadic adjustment. On this basis, the aim of this study is to determine the moderator role of employment status of women in the relationship between critical thinking disposition and dyadic adjustment of married people. The research group was composed of 242 spouses. The data were collected with Demographical Information Form, Critical Thinking Disposition Scale and Dyadic Adjustment Scale. The results showed that there was a correlation between critical thinking disposition and dyadic adjustment. According to the hierarchical regression analysis, there was no moderator role of employment status of women in the relationship between critical thinking disposition and dyadic adjustment.
Keywords: resilience; autonomous-related self; critical thinking